Medium effects in small systems : The bigger picture of heavy ion collisions - Le Roux, Chiara (Lund University, 2025)
The main focus of this thesis is on the puzzle of small systems, which arose when several signatures of the medium of quarks and gluons formed in heavy ion collisions were also observed in collisions of small systems, except for jet energy loss. To understand why that could be happening, papers I, III and IV focus on quantifying the sensitivity of different observables to medium interactions, whereas paper II explores another origin of anisotropies in small systems.
Keywords: heavy ions; jet quenching; small systems; color coherence